Pemanfaatan Live Streaming untuk Meningkatkan Daya Tarik Konsumen dan Penjualan Produk Body Care - Heta Fananiti, Edelweis; Deniaty Sholihah, Dewi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The purpose of this study was to determine the Utilization of Live Streaming to Increase Consumer Attraction and Sales of Body Care Products, With the right marketing strategy, products can be more competitive in the market while reaching a wider range of consumers, especially among young consumers who are familiar with technology. The collection technique in this service uses the AIDA model (Attention, Interest, Desire, Action) as a framework for analyzing the use of live streaming as a marketing strategy in increasing consumer attractiveness and sales of body care products. The results of the writing, The application of live streaming as a marketing strategy at CV Avero Indonesia has proven effective in attracting consumer attention and increasing sales. Live streaming increases interaction with the audience, consumer awareness of the product, and trust and emotional connection between the brand and consumers. It also expands audience reach through digital platforms. However, challenges such as dependence on technology stability and less engaging information delivery need to be overcome. Therefore, maintaining technological stability and enhancing content creativity are key to the success of the live streaming strategy going forward.